Analisis Perilaku Beternak Masyarakat terhadap Usaha Ternak Kambing di Kawasan Dataran Tinggi Wilayah Transmigrasi Lembatongoa Kecamatan Palolo Kabupaten Sigi - Maulita, Miftahul; Irfan, Mohamad; Mujayin, Yudi; Abdullah, Sirajuddin; Syahrir, Syahrir (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
This research aims to analyze the farming behavior of the transmigration community towards keeping goats in the highland areas in the Lembantongoa Transmigration area, Palolo District, Sigi Regency in September – November 2023. The research method used is a survey. Data collection techniques, namely field studies or observations through the interview process and filling out questionnaires. The variables observed in this research are economic (X1), social and cultural (X2), environmental (X3), food sources (X4), maintenance systems (Y1), income (Y2) and business development (Y3). The respondents used in this research were all transmigration communities who carried out goat breeding activities in the transmigration area, namely 74 breeders. The data collection technique uses a 1-5 Likert scale, while data analysis is carried out using quantitative descriptive methods. The results of the research showed that the highest average indicator scale proportion values were obtained for each latent variable, including: anticipation of plantation risk (X1.1), length of breeding (X2.3), temperature and humidity (X3.4), alternative feed (X4.5), cage cleanliness (Y1.5), farming income (Y2.1) and human resources (Y3.5). The conclusion of the research shows that the community's farming behavior regarding all latent variables has an average scale proportion that is in the good category.